THE RELATIONSHIP OF MEDIA LITERACY OF HOUSEWIVES IN RESPONDING TO HOAX NEWS VIA WHATSAPP MEDIA IN TAPOS II VILLAGE, TENJOLAYA DISTRICT, BOGOR REGENCY - Amalia, Nurul; Ernawati, Erna; Muslikhah , Febri Palupi (JURNAL SAHID DA'WATII, 2023)
The development of technology and information that is so widespread has made the spread of hoax information widespread, one of which is social media that is widely used by housewives, namely WhatsApp, which can have a bad influence so that media literacy is needed in responding to it. The purpose of this study was to determine the relationship between housewife media literacy in responding to hoax news via WhatsApp media in Tapos II Village and how big the relationship is. The method used is correlation with Rank Spearman analysis. The study involved 96 samples from 2479 populations based on the Simple Random Sampling technique and used a Likert scale questionnaire in collecting data. The results of the study show that 1) There is a relationship between media literacy of housewives in responding to hoax news via WhatsApp media based on a Sig value of 0.000 < ɑ 0.1. 2) Has a strong relationship with the Correlation Coefficient value of 0.536** and is included in a positive relationship, that is, when the media literacy of housewives is good, response to hoax news is also good, and when the media literacy of housewives is not good so responding to hoax news is also not good.